Exploring the evolution of supporter networks in the creation of new organizations - Newbert, Scott L.; Tornikoski, Erno T.; Quigley, Narda R. (Journal of Business Venturing, 2013)
It has long been argued that personal networks are important to entrepreneurial success; however, the nature of those networks is hotly debated, with scholars advocating that entrepreneurs create networks of strong ties, weak ties, or a mix of both strong and weak ties. Given that empirical support for all three camps can be found in the literature, it is unclear whether there is an optimal network structure. We suspect that one reason for this ambiguity is the static view of personal networks that empiricists have typically taken in previous studies. In response, we hypothesize that a nascent entrepreneur’s network of individuals who provide resources to the emerging organization (i.e., supporters) may take any of the structural forms identified above at any given point time during the emergence phase, but in order for that entrepreneur to succeed in creating a new organization, the strength of the ties comprising the supporter network must become more heterogeneous over time. Using data from the Panel Study of Entrepreneurial Dynamics I (PSED I), we conduct a longitudinal analysis that examines how supporter networks of successful and unsuccessful nascent entrepreneurs evolve over time. Our results suggest that the more heterogeneous the strength of nascent entrepreneurs’ ties to supporters become throughout the emergence phase, the more likely they will succeed in creating new organizations. We conclude by discussing the implications of our findings for both academics and practitioners.